Green methane production: Kinetic and mass transfer modeling in a batch process. (May 2021) - Jafari, Seyed Ali; Osfouri, Shahriar; Azin, Reza
Abstract: One of the major issues in biomethanation studies, especially a batch strategy without mixing, is gaseous substrate mass transfer between gas and liquid phases. The strategy can be assumed as a simplified form of a stagnant underground gas reservoir. Hydrogen gas, as the limiting substrate, plays significant role in biomethanation. Being informed of hydrogen content diffused within the liquid phase for calculating percentage of active volume, help researcher to make a proper decision on bioreactor design or adjusting process parameters. For this purpose, a mass transfer modelling was developed which strengthened with a set of optimized biokinetic parameters. Parameter optimization was accomplished with the help of a predefined optimization algorithm and using a set of experimental data with the source of literature. Active volume calculation was successfully performed via the verified model and response surface methodology was served for maximizing it under variety of process conditions. It was found that the bioreactor height to width ratio significantly affected on active volume followed by pressure and temperature. In addition, working with a bioreactor with a circle cross section, in comparison with a square one, improved the maximum active volume up to 43% due to providing higher surface area for mass transfer. Sensitivity analysis verified the previous findings and revealed that higher pressures and temperatures linearly increased the active volume while increasing the bioreactor height to width ratio exponentially decreased the response. Furthermore, a wide bioreactor have potential to promote active volume up to 72% rather than a vertical one. Graphical abstract: Image 1 Highlights: Key bio-kinetic parameters were globally optimized for vast experimental conditions Pressure linearly influenced on hydrogen diffusion within the liquid phase Active volume was most affected by height to width ratio and diffusivity parameters A cylindrical geometry improved percentage of active volume 43% more than a cube one Higher pressures and temperatures in a wide bioreactor make process more favorable